2019
DOI: 10.1111/jai.13964
|View full text |Cite
|
Sign up to set email alerts
|

A new record of Iranian subterranean fishes reveals the potential presence of a large freshwater aquifer in the Zagros Mountains

Abstract: A new locality is reported for the Iranian subterranean fishes Garra typhlops and Garra lorestanensis (and probably Eidinemacheilus smithi), near the village Tuveh in the Dez River drainage. The site is 31 km straight‐line distance away from the only other known locality where these species have been observed previously. The finding suggests the presence of a sizeable subterranean aquifer system in the Tigris drainage extending for between 31 and 162 km.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
0
18
2
Order By: Relevance
“…The karst aquifer feeding the Ganow spring, the type locality of A. ismailsezarii sp. nov., also harbors three described species of cave fish (Mousavi-Sabet et al 2016;Vatandoust et al 2019) as well as yet-undescribed species of gastropods (in first author collection). This paper contributes a piece in the puzzle of the Iranian cave biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The karst aquifer feeding the Ganow spring, the type locality of A. ismailsezarii sp. nov., also harbors three described species of cave fish (Mousavi-Sabet et al 2016;Vatandoust et al 2019) as well as yet-undescribed species of gastropods (in first author collection). This paper contributes a piece in the puzzle of the Iranian cave biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…We know of only 43 obligate groundwater species from Iran, despite the fact that 10.5% of the country (compared with approximately 1.7% of Europe) is underlain by carbonate rock formations. The obligate groundwater fauna includes four fish species, 23 amphipods of the genus Niphargus Schiødte, 1847, 12 copepods, one oligochaete, one gastropod and two isopods (Cichocka et al 2015;Mousavi-Sabet et al 2016;Malek-Hosseini and Zamani 2017;Vatandoust et al 2019;Bargrizaneh et al 2021;Malek-Hosseini et al 2021). The only two obligate groundwater isopods known from Iran are Microcharon raffaellae Pesce, 1979 (Lepidocharontidae) collected from a well in Pliocenic sandstone and clay at Shahr-e-Kord city, Chaharmahal and Bakhtiari Province, and Stenasellus tashanicus Khalaji-Pirbalouty, Fatemi, Malek-Hosseini & Kuntner, 2018 (Stenasellidae) collected from Tashan karstic cave in Khuzestan province (Pesce 1979;Khalaji-Pirbalouty et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Mahjoorazad and Coad (2009) reported a blind subterranean fish (claimed to be Iran cave barb G. typhlops ) from a locality in the Seimareh River drainage (Karkheh River) 131 km from the cave barb type locality (i.e., the locality where the species were originally described; see Figure 3) in the Dez River drainage. Vatandoust et al (2019) reported a new locality for the Iran cave fish ( G. typhlops , G. lorestanensis , and E. smithi ) 31 km from the cave barb type locality (Tuveh Spring, Dez River drainage; Figure 3) and, based on a report by Mahjoorazad and Coad (2009), hypothesized that there may be an aquifer system hosting the blind cave fish with dimensions of 31–162 km. Based on this relatively wide geographical range for the Iran and Lorestan cave barbs, Vatandoust et al (2019) suggested the need for reconsideration of conservation category of these fishes in the IUCN Red List of threatened species, as one of the criteria used to determine conservation rank of each species is the extent of its range.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this relatively wide geographical range for the Iran and Lorestan cave barbs, Vatandoust et al (2019) suggested the need for reconsideration of conservation category of these fishes in the IUCN Red List of threatened species, as one of the criteria used to determine conservation rank of each species is the extent of its range. However, in reports by Mahjoorazad and Coad (2009) and Vatandoust et al (2019), it was apparently assumed that the cave barb species in other localities (in the Karkheh River drainage) were also G. typhlops or G. lorestanensis and that these species had similar distributions within the subterranean habitat. Hashemzadeh Segherloo et al (2018) reported that, in contrast to the Iran cave barb, which was observed during most of the year, the Lorestan cave barb was mostly captured at the cave barb type locality during the fluvial period (late winter‐early spring) when water flows out from the subterranean habitat.…”
Section: Introductionmentioning
confidence: 99%
“…Globally, subterranean environments have been colonized by several groups of animals, for example, fishes, amphibians, molluscs, and many arthropod groups (Vandel, 1964). Iran has some of the largest cave systems in the world (Raeisi et al, 2012;Vatandoust et al, 2019), yet most of them are poorly investigated. Troglobiotic representatives of fishes, millipedes, spiders, crustaceans, and snails are already recorded from Iranian caves (Bargrizaneh et al, 2021;Fatemi et al, 2019;Malek-Hosseini & Zamani, 2017).…”
Section: Introductionmentioning
confidence: 99%